Sound Embodiment of Rene Eespere’s Piano Cycles: Experience of Performance Analysis - Pylypenko, Stanislav (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
The novelty of the article lies in expanding knowledge about the contemporary outstanding musicians using the example of the performance analysis of the piano cycles of the Estonian composer Rene Eespere in the context of their sound embodiment. The purpose of the article is to identify the specificity of the sound embodiment of R. Eespere’s piano cycles: “4 ostinato” and “24 preludes” (first book). The research methodology is based on an integrated approach that combines the principle of musical-theoretical and performance analysis, which are necessary for solving the tasks set in the article. Results and conclusions. The article examines the creativity of the Estonian composer Rene Eespere on the example of his piano cycles “4 ostinato” and “24 preludes” (first book). The paper detects the key tasks that arise before the performer and contribute to the sound embodiment of the proposed compositions. The basis for this research was the personal performance experience of the article’s author; work in the class of Professor S. Yushkevich; audio and video recordings of piano cycles, as well as direct communication with R. Eespere in the format of electronic correspondence. The article reveals the main features of his composer style, which synthesizes the traditions of Western European and national culture. In addition, the work shows R. Eespere’s gravitation towards minimalism in music. Ostinato is a characteristic manifestation of the composer’s creative thinking in these piano cycles. This compositional technique determines the different emotional orientation of each piece. The article also examines the variants of texture formulas in the proposed piano opuses, which require mobility from the performer in changing pianistic techniques. Analytical study of these works made it possible to identify the following performance tasks: the stability of intricate rhythmic complexes, subtle dynamic nuances, timbre variety, moderate pedalling, as well as the use of expressive key touch. In general, the sound embodiment of the piano cycles of the Estonian composer R. Eespere brings out new facets in understanding of musical context and contributes to the formation of a performance experience so valuable for the development of modern piano art.